Access to Health Insurance, Barriers to Care, and Service Use among Adults with Disabilities - Anna S. Sommers (SAGE Publishing, 2006)
No studies to date have examined access to insurance coverage or medical care for a broadly defined population of uninsured nonelderly adults with disabilities. This analysis uses the 2002 National Survey of America's Families to examine access to coverage, access to care, and service use for a large sample of adults with disabilities, with a focus on the uninsured. All disabled groups reported unmet need and service use greater than their nondisabled counterparts with the same insured status. Access to coverage was most problematic for low-income adults with work limitations but no other indication of disability, with over one-third uninsured. This group deserves greater policy attention.